Online patient portal use by caregivers in pediatric oncology: Are we widening sociodemographic disparities?. Issue 12 (28th September 2021) - Schultz, Corinna L.; McCahan, Suzanne M.; Lewis, Amanda M.; Bunnell, H. Timothy; Alderfer, Melissa A.
Abstract: Background: Financial and regulatory incentives have encouraged and increased the availability of online patient portals that provide caregivers access to their child's electronic health records (EHR). Such access is believed to promote better engagement and outcomes of care. Little is known about the use of portals by caregivers of children with cancer. This study sought to examine whether sociodemographic and clinical care variables are associated with portal activation in a pediatric oncology sample. Methods: Sociodemographic and clinical characteristics were extracted from the EHR of pediatric oncology patients treated for their first cancer in the Nemours Center for Cancer and Blood Disorders between 2012 and 2017. A Child Opportunity Index (COI) was calculated based on home zip code. Characteristics of children whose caregivers did and did not activate the portal were compared. Results: Sixty‐six percent of caregivers activated a portal account with a peak within 90 days of diagnosis. In logistic regression, caregivers with a younger aged child, spoke English, lived closer to the hospital, lived in higher COI area, with longer treatment length, and more radiology tests had greater odds of portal activation. Those with private health insurance or White race were overrepresented among those who activated an account in univariate analysis. Conclusion: The majority of caregivers of children with cancer activate portal accounts; however, differences in sociodemographic and clinical variables across those who did and did not activate accounts emerged. As portals become ubiquitous, we must understand how they are used and mitigate widening inequities caused by disparate portal use.